Mechanisms of Insulin Signaling as a Potential Therapeutic Method in Intestinal Diseases - Sara Jarmakiewicz-Czaja; Aneta Sokal-Dembowska; Katarzyna Ferenc; Rafał Filip (Cells)
Gastrointestinal diseases are becoming a growing public health problem. One of them is inflammatory bowel disease (IBD), which includes ulcerative colitis (UC) and Crohn’s disease (CD). The incidence of IBD is increasing in developing countries and declining in developed countries, affecting people of all ages. Researchers have been exploring new treatment options including insulin signaling pathways in the inflammation of the gastrointestinal tract. It seems that a better understanding of the mechanism of IGF-1, GLP-1 and TL1A on the gut microbiota and inflammation may provide new advances in future therapeutic strategies for patients with IBD, but also other intestinal diseases. This review aims to synthesize insights into the effects of GLP, IGF and anti-TL1A on inflammation and the gut microbiota, which may enable their future use in therapy for people with intestinal diseases.